Effect of Ramadan fasting in late pregnancy on pregnancy outcome - Abd E.G. Eldeen Al Darwish; Mahmoud I.A. Elrahsidy; Asmaa K. Nasr (Al-Azhar Assiut Medical Journal)
Background Fasting from food and drink is observed during the Muslim holy month of Ramadan, which commences at sunrise and concludes at sunset. This study aimed to study the effects of fasting throughout Ramadan in late pregnancy on pregnancy outcome. Patients and methods This prospective observational research was done on 200 pregnant cases attending outpatient clinic and inpatient admitted to Department of Obstetrics and Gynecology in both Isis hospital and Al Azhar University Hospitals (Assiut). All pregnant women had been divided into two groups. Results There was no statistically significant variance among group A and group B concerning height of baby (cm), birth weight (kg), head circumference (cm), Mid Arm Circumference (cm) and Weight of Placenta (g) P= 0.521, 0.193, 0.782, 0.816, 0.345) respectively. There was no statistically significant variance among group A and group B concerning Middle cerebral Artery PI in start of Ramadan P=0.652 and Middle cerebral Artery PI in the end of Ramadan P=0.822. There was no statistically significant variance among group A and group B concerning Amniotic fluid Index(AFI) in start of Ramadan P= 0.550 and AFI in the end of Ramadan P= 0.431. Conclusion Ramadan fasting does not negatively impact pregnant women’s health, including head circumference, newborn weight, and height. It also does not harm the fetus, as indicated by normal Doppler indices and amniotic fluid levels. However, these findings apply to young, healthy women.